Nanotechnology Fundamentals and applications - Manasi Karkare (New Delhi I K International Pvt Ltd, 2019)
Potential of Nanotechnology is immense and encompasses virtually every field of life. Technologists and researchers all across the globe have realized this and call it the Technology of the Future. the book is intended to develop interest amongst students of all branches of Engineering and incumbent researchers so that they get to know fundamentals of the subject.The books deals with all the aspects of nanotechnology and its fundamentals and applications, i.e. Nanotechnology, tools and techniques, nanomaterials, nanocomputers, nanocomposites, risks related with the use of nanotechnology and its relation with the environment. Applications of nanotechnology in textiles, solar power, electronics, space explorations and in communication find a reasonable place in the book